Effectiveness and contribution of the Ethiopian Sport Academy (ESA) to Ethiopian National Athletics Team - Jembere (Ph.D) , Ayyantu; Eba (Ph.D), Amanu; Fikadu (Ph.D), Tekalegn; Teka (Ph.D), Meskerem; Chalchisa (Ph.D), Emebet; Wondirad (Ph.D), Samson (ETHIOPIAN JOURNAL OF SPORT SCIENCE, 2024)
ESA has been taking the lions’ share in shaping the success of the Ethiopian Athletics National Team through nurturing talent, providing specialized coaching, leveraging altitude benefits, fostering group dynamics, aligning with cultural norms, and producing remarkable success stories on the Ethiopian athletics. This study was focused to assess the effectiveness and contribution of ESA to the Ethiopian National Athletics National Team. The study used mixed-methods approach research design. ESA has (N = 2) campuses and sampled athletes (n = 222) were selected using proportional sampling technique. Outcome variable of the study was contribution of the athletes to the Ethiopian national athletics team. Predictor variable was effectiveness of ESA. The primary data collection instruments such as standardized questionnaire, semi-structured interview, and focus group discussion was piloted and administered to the athletes. SPSS and Nvivo software’s used to process quantitative and qualitative data respectively. Structural Equation modelling (ESA) was used to analyse effectiveness of sport academy. The result of the study shows that skilled workforce, stability, availability of information, productivity, plans, resources and flexibility significantly contribution to the effectiveness of sport academy at p < 0.05. The effectiveness of ESA enables them to produce world class middle and long distance runners to the Olympic level. However, there are remaining works on short distance, jumping and throwing events. The study recommends ESA management to produce sprinters, jumpers and throwers aligning with their sport nutrition as well as hire professionals like f physiotherapist and sport psychologist